Morphological changes in a macro-tidal estuary during extreme flooding events - Du, Yixiao; Cheng, Zhixin; You, Zaijin (Frontiers in Marine Science, 2023)
River discharge is a controlling factor in estuarine morphological changes, the estuarine topography can be greatly shifted even within one flooding event. However, the mechanism of morphological changes in mountain-stream macro-tidal estuaries during wet seasons is not fully understood. Taking the Yalu River Estuary (YRE), China as an example, this study aims to explore the effects of extreme flooding events on estuarine morphology. An improved Finite Volume Coastal Ocean Model (FVCOM) model was applied in the YRE to reproduce the distribution of bed sediment erosion and deposition during dry years, normal years, wet years. Sensitivity tests were conducted to assess the responses of the estuarine system to river discharge. The influence of the Yalu River on the magnitude of estuarine bed change was examined. With the increase of river discharge, bed thickness in the estuarine main channel increased first and then decreased after the threshold of 0.4 x 104m3/s. Simultaneously, the density stratification became stronger with the increase of runoff. Then the vertical mixing of water was weakened after a certain threshold, which in turn enhances the density stratification, and changes the law of the location change of the Estuarine Turbidity Maxima (ETM). In addition, river effects contribute to nearly half of the bed erosion under 0.6 x 104m3/s (flooding with fifty-year return period). The ETM extended and moved around 8km seaward during flooding events. The West River channel experienced strong siltation, which is more significant during flood events. Results from this study demonstrate that estuarine circulation plays a key role on morphology change, the magnitude of bed thickness erosion can reach 22% of the total initial thickness during one flooding event. This rapid change is a threat to the stability of port infrastructures and actions should be made to maintain the safety of coastal construction.